Review on Chemical treatment of Industrial Waste Water - OP Sahu; PK Chaudhari (Journal of Applied Sciences and Environmental Management, 2013)
Industrialization played an important role for scio-economy of the country. Generally, a lot of water is used and lot of wastewater generated from industries due their processes and washing purpose. A large number of chemicals are used for the production of potable water and in the treatment of wastewater effluents. In potable water treatment chemicals such as inorganic salts and polymeric organic coagulants are used for primary coagulation, as coagulant aids and for sludge dewatering; lime and soda ash allowed for pH correction and water stabilization; caustic soda is used for pH adjustment, powdered activated carbon (PAC) can remove taste and odour compounds and micro pollutants such as atrazine, bentonite aid's coagulation, and ammonium hydroxide is used in chloramination. The main object of review is focus on research work done as well as the basic concept behind treatment and application by the researcher on different industry's waste-water treatment. ©JASEM